Addressing water-related health risks in agroecosystems - Boelee, Eline; Grace, Delia (International Livestock Research Institute, 2012)
We acknowledge financial support to this research by ACIAR, DFID, ESPA, ESRC,NERC and the CGIAR Research Program on Agriculture for Nutrition and Health